Preparation method and use of MOFs-based composite pretreatment material for eliminating CAP interference
By using MOFs-based composite materials to treat spicy hot pot base, combined with SERS technology, the problem of CAP interference is solved, and the accurate quantity detection of α-SOH is achieved, which improves the accuracy and stability of the detection.
Patent Information
- Application Number
- CN202210750180.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-06-29
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2042-06-29
AI Technical Summary
The prior art is difficult to effectively eliminate the Raman spectral detection signal interference of capsaicin (CAP) on hydroxy-α-rosaicin (α-SOH) in spicy hot pot base, resulting in difficulty in quantitative detection.
The metal-organic framework (MOFs)-based composite material is used as the pretreatment material, and the magnetically modified metal-organic framework is coated with amidated polysulfone to process the object to be tested, and the magnet adsorption and separation are used, combined with surface enhancement Raman (SERS) technology to achieve quantitative detection of α-SOH.
It effectively eliminates the interference of CAP on Raman detection signal of α-SOH, improves the accuracy and stability of quantitative detection of α-SOH in spicy hot pot base, and is suitable for real-time and on-site detection in actual production.
Smart Images

Figure CN115078330B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of rapid food detection, and in particular relates to a preparation method and application of a MOFs-based composite pretreatment material for eliminating CAP interference. Background Art
[0002] Sichuan hotpot is famous for its spicy flavor and is loved by consumers. Hydroxyl-α-sanshool (α-SOH) is the most important representative ingredient that produces the spicy flavor. Its content is an important indicator for measuring the flavor quality of spicy hotpot base, and plays a key role in the flavor regulation and standardized production of spicy hotpot base. Therefore, it is very important to achieve rapid quantitative detection of α-SOH in spicy hotpot base.
[0003] The common method for detecting numbing substances is high performance liquid chromatography, but its operating procedure is relatively complicated and cannot achieve portable rapid detection. A patent uses Raman spectroscopy to achieve rapid detection of numbing substances in pepper extracts (202010112255.2). However, the focus of Raman detection of numbing substances in spicy hot pot base is that the Raman characteristic peaks of capsaicin (CAP) and α-SOH will have serious overlaps and cannot achieve accurate quantification of α-SOH. In addition, although there is a patent that uses polyphenol oxidase to treat spicy hot pot base to eliminate the Raman signal interference of CAP on α-SOH (202011314447.8), due to the short storage period of natural enzymes, their activity is greatly affected by the source and detection environment (temperature, pH, etc.), which will bring limitations to the application of the above method. Therefore, it is necessary to develop a method that can stably eliminate the interference of CAP in spicy hot pot base to achieve Raman spectroscopy detection of α-SOH. Summary of the invention
[0004] The present invention aims to construct a composite material based on a metal organic framework (MOFs) to eliminate the Raman signal interference of CAP on α-SOH, and thereby establish a surface enhanced Raman (SERS) method that can quickly qualitatively and quantitatively detect α-SOH in spicy hot pot base.
[0005] To achieve the above objectives, the technical solution of the present invention includes: using an amidated polysulfone-coated magnetically modified metal-organic framework to treat the object to be tested (hot pot base), using a magnet to adsorb and separate the solid and then mix it with a SERS substrate, collecting Raman spectral signals, and realizing the quantitative detection of α-SOH in spicy hot pot base.
[0006] The present invention provides a MOFs-based composite material for eliminating CAP interference in spicy hot pot soup base and realizing α-SOH Raman quantitative detection, and the specific steps are as follows:
[0007] (1) Preparation of metal organic framework (MOFs) material: adding MOFs material to methanol for ultrasonic washing, collecting solid material by centrifugation after washing, and drying, and redispersing the dried product in methanol to obtain a metal organic framework suspension, which is recorded as suspension A;
[0008] (2) dissolving an iron salt in deoxygenated pure water and stirring to obtain an iron salt solution, then adding ammonia water dropwise to the iron salt solution, and continuing to stir after the addition to obtain a dispersion, the obtained dispersion is centrifuged to obtain a precipitate, and after washing and centrifugation, the precipitate is dispersed in water to obtain a magnetic nanoparticle suspension, which is recorded as suspension B;
[0009] (3) adding suspension A to suspension B, and heating the mixture to obtain a solid suspension; collecting the solid suspension by centrifugation and ultrasonic washing, and then drying the solid suspension to obtain a dried product, which is dispersed in N,N-dimethylformamide (DMF) to obtain a metal organic framework suspension modified with a magnetic material, which is recorded as suspension C;
[0010] (4) First, amidated polysulfone (PIPSF) is dissolved in N,N-dimethylformamide (DMF) to obtain a PIPSF solution; then the suspension C is added and mixed, and stirred at room temperature to obtain a MOFs-based composite material mother liquid; a spray gun device is used to make the MOFs-based composite material mother liquid generate droplets and solidify and precipitate in water, and a spherical precipitate is obtained after filtering; that is, a MOFs-based composite pretreatment material is obtained;
[0011] Furthermore, in step (1), the MOFs material is one or more of HKUST-1, ZIF-67, ZIF-8, Fe-BTC, or MIL-101 (Fe); the particle size of the MOFs material is 0.1 to 5 μm;
[0012] The ultrasonic washing time is 1 to 3 minutes; the centrifugal conditions are 3000 to 8000 rpm / min, 5 to 10 minutes; the drying conditions are: 30 to 60° C., 6 to 12 hours; the concentration range of the suspension A is 0.1 to 10 mg / mL.
[0013] Furthermore, in step (2), the iron salt is one of ferrous chloride tetrahydrate or ferric chloride hexahydrate or a mixture of the two; the concentration of the ammonia water is 20% to 30%; and the dosage ratio of the iron salt, deoxygenated pure water, ammonia water and water is (1 to 2) g: (40 to 50) mL: (5 to 10) mL: (40 to 50) mL.
[0014] Further, in step (2), the stirring temperature condition for the iron salt solution is 35°C; the stirring time is 2 to 3 hours; the centrifugation conditions are 15000 rpm / min, 10 to 30 minutes; the washing conditions are: adding the precipitate to water for washing; the concentration range of the suspension B is 10 to 30 mg / mL; the dispersoid of the suspension B is ferroferric oxide (Fe 3 O 4 ).
[0015] Furthermore, in step (3), the dosage ratio of the suspension A to the suspension B is (30-40) mL: (10-20) mL; the concentration range of the suspension C is 10-20 mg / mL;
[0016] The heating temperature is 50-100°C and the time is 10-20h; the centrifugal conditions are: the rotation speed is 3000-6000r / min and the time is 10-15min; the operation of ultrasonic washing is: adding the precipitate after centrifugation into water for ultrasonic cleaning; the drying conditions are: 25°C, 24h.
[0017] Furthermore, in step (4), the dosage ratio of PIPSF to DMF is (10-20) g: 100 mL; the volume ratio of the PIPSF solution to the suspension C is (1-5): (1-10); the stirring time at room temperature is 12-24 h; the condition for the MOFs-based composite material mother liquid to generate droplets is: specifically, droplets are generated by a semi-continuous spray gun device with a nozzle size of 800 μm; the operation of obtaining the spherical precipitate is: filtering using a 5 μm nylon filter;
[0018] Furthermore, in step (4), the specific synthesis steps of PIPSF are as follows: dissolving 20g of polysulfone (PSF) in 200mL of dichloromethane, and then dropping a mixture of 20g of chloromethyl ether and 1.5g of anhydrous zinc chloride thereto to obtain chloromethylated polysulfone (CMPSF); weighing 10g of chloromethylated polysulfone and dissolving it in DMF, and then adding 200mL of a mixed solution of phthalimide, sodium hydride and DMF (the dosage ratio is 18g:8g:74mL); heating and condensing the reaction mixture at 80°C for 10h, and then cooling the reaction mixture to room temperature; precipitating the product with a methanol solution, and then repeatedly washing it with distilled water, and drying it in a vacuum drying oven at 60°C for 24h, and the obtained product is PIPSF.
[0019] Based on the use of MOFs-based composite pretreatment materials that can eliminate CAP interference for the detection of α-SOH in hot pot base, the specific steps are as follows:
[0020] (1) Draw the α-SOH standard curve:
[0021] First, α-SOH standard solutions of different concentrations are prepared; then the prepared MOFs-based composite pretreatment material is added into water to obtain a MOFs-based composite pretreatment material solution;
[0022] Take V 1 α-SOH standard solution with different concentrations by volume, and V 2 The MOFs-based composite pretreatment material solution was mixed with 200 volumes of MOFs-based composite pretreatment material solution (one concentration of α-SOH standard solution corresponds to one MOFs-based composite pretreatment material solution), and the mixed solution was incubated at room temperature; after incubation, the mixture was separated by a magnet, and the mixture was collected and redissolved in water to obtain pretreatment standard solutions of different concentrations of α-SOH; finally, V 4 Bulk gold and silver core-shell nanomaterials as SERS substrates, with V 3 The mixed solution of 100 volume of pre-treatment standard solution was added dropwise to the silicon wafer, and after drying, a portable Raman spectrometer was used to perform spectral scanning to obtain a Raman spectrum. The characteristic Raman shift was used as the quantitative reference peak, and the characteristic peak intensity value I was recorded. A standard curve was established based on the relationship between the concentration of α-SOH and the peak value at the characteristic Raman shift.
[0023] (2) Raman detection of samples to be tested:
[0024] Weigh the spicy hot pot base sample to be tested, record the mass as m, and add V 0 volume of ethanol, placed in an ultrasonic instrument for extraction to obtain a crude extract; the crude extract was centrifuged and the supernatant was collected, concentrated by a rotary evaporator, and diluted with ethanol to obtain a test solution, which was stored at low temperature for later use; V 1 The volume of the test liquid and V 2 The volume of MOFs-based composite pretreatment material solution was mixed and incubated at room temperature; after incubation, the solid mixture was separated by a magnet, and the solid mixture was collected and redissolved in water to obtain a pretreatment test solution; finally, V 4 Bulk gold and silver core-shell nanomaterials as SERS substrates, with V 3 The pre-treated test solution of 1000 volumes is mixed and then dripped onto the silicon wafer. After drying, a portable Raman spectrometer is used to perform spectral scanning, and the obtained spectrum is baseline optimized to obtain a Raman spectrum.
[0025] (3) Quantitative determination:
[0026] According to the Raman spectrum of the test liquid obtained in step (2), the characteristic Raman shift is used as the quantitative reference peak, the quantitative reference peak intensity value is recorded, and the concentration of α-SOH in the test liquid is obtained according to the α-SOH standard curve of step (1), which is recorded as c, and the content X of α-SOH in the spicy hot pot base sample is further calculated according to the formula:
[0027]
[0028] X: the content of α-SOH in spicy hot pot base sample, mg / g;
[0029] c: The concentration of α-SOH in the test solution obtained according to the standard curve, mg / mL;
[0030] V 0 : Volume of the test liquid, mL;
[0031] m: Mass of spicy hot pot base sample, g.
[0032] Furthermore, in step (1), the concentration of the MOFs-based composite pretreatment material solution is 0.1 to 10 g / mL; the α-SOH standard solution uses ethanol as a solvent and has a concentration range of 0.1 to 10 mg / mL; the concentration of the gold and silver core-shell nanomaterial is 0.1 to 0.5 nM; the V 1 、V 2 、V 3 and V 4 The volume ratio is 1:(1-3):1:1; the collected solid is redissolved in water to obtain pretreatment standard solutions of different concentrations of α-SOH in a concentration range of 0.1-10 g / mL;
[0033] Furthermore, in step (1), the amount added to the silicon wafer is 1 to 10 μL; the incubation time at room temperature is 1 to 10 min; the quantitative reference peak is 1630 cm -1 , generated by the vibration of unsaturated fatty chains; the parameters of the portable Raman spectrometer are as follows: the Raman spectrometer emits a laser wavelength of 735nm, a fixed laser power of 5mW, and a scanning range of 500-2500cm -1 , the integration time is 1 to 10 s, and each sample is scanned 10 times to take the average value;
[0034] Furthermore, in step (1), the specific synthesis steps of the gold-silver core-shell nanomaterial are:
[0035] a. Prepare gold nanorod colloid; in a constant temperature water bath at 25-30°C, add 0.6 mL of sodium borohydride (NaBH 4 ) was added to 10 mL of chloroauric acid (HAuCl 4 , 0.25 mM) and 0.725 g of hexadecyltrimethylammonium bromide (CTAB) in a mixed solution, stirred for 2 min and incubated for 2 h under light-proof conditions to obtain a tea-brown seed solution; 5 mL of CTAB (0.2 M) and 0.07 mL of silver nitrate AgNO 3 (2~6mM) After mixing evenly, add 5mL of HAuCl 4(1mM) were mixed in sequence, the solution turned golden yellow, 0.012mL ascorbic acid (0.0788M) was added under stirring to mix the solution evenly, the solution turned colorless, and a gold nanorod growth solution was obtained; the tea brown seed solution prepared above was added to the gold nanorod growth solution, and the solution was stored at room temperature and protected from light for 12h, and the solution gradually changed from colorless to dark blue; the dark blue solution was centrifuged at 8000rpm / min for 5-10min, the supernatant was removed to obtain a precipitate, and the precipitate was ultrasonically washed with ultrapure water to remove excess CTAB, and then the precipitate was dispersed in 10mL of ultrapure water to obtain a gold nanorod colloid;
[0036] b. Preparation of gold and silver core-shell nanomaterials: 2 mL of gold nanorod colloid prepared in step a and 4 mL of hexadecyltrimethylammonium chloride (CTAC, 20 mM) were mixed evenly and stirred at 60 °C for 20 min; then 5 mL of AgNO 3 The mixed solution of 5 mL of 1% CTAC (1-5 mM) and 5 mL of CTAC (40 mM) and ascorbic acid (0.05 M) was heated and stirred for 4 h, and the solution gradually turned gray-green; the synthesized gray-green solution was then immersed in ice water for cooling, centrifuged at a speed of 3000-6000 rpm / min for 5-10 min, and the precipitate after removing the supernatant was ultrasonically washed with ultrapure water. The washed precipitate was redispersed in water to obtain gold-silver core-shell nanomaterials with a concentration of 0.1-0.5 nM.
[0037] Furthermore, in step (2), the ratio of the spicy hot pot base sample to ethanol, i.e., m:V 0 =(10-20) g:(20-60) mL; said V 1 、V 2 、V 3 and V 4 The volume ratio is 1:(1-3):1:1; the amount added to the silicon wafer is 1-10 μL;
[0038] Furthermore, in step (2), the extraction time is 5 to 20 minutes; the conditions for centrifugation of the crude extract are: 1000 to 3000 rpm / min, time is 3 to 10 minutes; the conditions for low-temperature storage are -4°C; the time for incubation at room temperature is 1 to 10 minutes; the parameters of the portable Raman spectrometer are as follows: the Raman spectrometer emits a laser wavelength of 735 nm, a fixed laser power of 5 mW, and a scanning range of 500 to 2500 cm -1 , the integration time is 1 to 10 s, and each sample is scanned 10 times to take the average value;
[0039] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0040] (1) The present invention effectively eliminates the interference of CAP on the Raman detection signal of α-SOH in spicy hot pot base by preparing a MOFs-based composite material.
[0041] (2) Compared with the existing method of using natural enzymes to decompose CAP in food matrices, the MOFs composite material prepared by the present invention has high stability and a wider temperature application range, providing reliable guarantee for the real-time and on-site detection of numbing substances in actual production. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 This is a stability test diagram of the MOFs-based composite pretreatment material prepared in Example 1.
[0043] Figure 2 Surface enhanced Raman spectra of α-SOH standards with concentrations ranging from 0.1 mg / mL to 10 mg / mL.
[0044] Figure 3 It is the Raman spectra of numbing substances in any two spicy hot pot base samples and the Raman spectra after being treated with MOFs-based composite pretreatment materials; wherein sample a is Haidilao spicy hot pot base, sample b is the pretreated test liquid of Haidilao spicy hot pot base, sample c is Xiabu Xiabu spicy hot pot base, and sample d is the pretreated test liquid of Xiabu Xiabu spicy hot pot base. DETAILED DESCRIPTION
[0045] In order to more clearly illustrate the content of the present invention, the present invention is described in detail below in conjunction with embodiments, but the present invention is not limited to these embodiments.
[0046] Embodiment 1:
[0047] 1. Experimental samples, main reagents and instruments
[0048] Samples: 6 different spicy hot pot bases purchased from the market were used as test objects; sample number 1 was Hong 99, sample number 2 was Haidilao, sample number 3 was Qiaotou, sample number 4 was Mala Space, sample number 5 was Dahongpao, and sample number 6 was Xiabu Xiabu.
[0049] Standard product: α-SOH was purchased from Chengdu Medson Technology Co., Ltd. with a purity of ≥98%.
[0050] Membrane material: Polysulfone (PSF) was purchased from Tianjin Motimo Technology (Motimo) and used as the original membrane material.
[0051] Reagents: All the water used in the experiment was deionized water, and all the experimental reagents were analytical grade.
[0052] Instrument: Portable Raman spectrometer (SR-510Pro, Shanghai Weihai Optical Instrument Co., Ltd.).
[0053] 2. Preparation of MOFs-based composite pretreatment materials
[0054] (1) The MOFs material in step (1) is a mixture of HKUST-1 and ZIF-8 (ZIF-8 / HKUST-1), and the specific preparation method is as follows:
[0055] Add 0.1 g polyvinylpyrrolidone (PVP) to 40 mL of CuCl 2 The mixture was stirred in a 2.5 mL (2.5 mM) solution until uniformly mixed, and then 2.5 mL of a NaOH solution (0.2 M) was slowly added, and the mixture was kept at room temperature for 5 min. Then 2.5 mL of an ascorbic acid solution (0.1 M) was added dropwise, and the mixture was kept at room temperature for 5 min after the addition was completed. The mixture was added to a mixture containing a PVP solution (0.4 g, 60 mL) and a methanol solution of trimesic acid (0.2 g, 4 mL), and the mixture was stirred at room temperature for 16 h to obtain HKUST-1.
[0056] Then 5 mL of HKUST-1 was diluted to 50 mL with methanol, and a PVP methanol mixed solution (PVP 350 mg, methanol 10 mL) was added, and stirred at room temperature for 12 h to obtain a PVP / HKUST-1 suspension; 0.5 mL of the PVP / HKUST-1 suspension and 0.372 g of Zn(NO 3 ) 2 6H 2 O was dispersed in 50 mL of methanol, and then 50 mL of a methanol solution containing 0.103 g of 2-methylimidazole was added, and the mixture was reacted at room temperature for 24 h. The lower layer product was collected after centrifugation at 3000 rpm / min for 10 min to obtain ZIF-8 / HKUST-1.
[0057] ZIF-8 / HKUST-1 was added to 100 mL of methanol and ultrasonically washed for 3 min. After washing, the solid material was collected by centrifugation at 3000 rpm / min for 10 min and dried in an oven at 45 °C for 8 h. The dried product was redispersed in methanol to obtain a ZIF-8 / HKUST-1 suspension with a concentration of 0.8 mg / mL.
[0058] (2) The iron salt in step (2) is ferrous chloride tetrahydrate (FeCl 2 ·4H 2 O) and ferric chloride hexahydrate (FeCl 3 6H 2 O) mixture, in order to carry out specific operations:
[0059] 0.438 g of FeCl 2 ·4H 2O and 1.192 g of FeCl 3 6H 2 O was dissolved in 40 mL of deoxygenated pure water and stirred at 35°C to obtain an iron salt solution; 8 mL of 28% ammonia water was added dropwise to the iron salt solution, and stirring was continued for 2 hours after the addition was completed to obtain a dispersion liquid, and the obtained dispersion liquid was centrifuged at 15000 rpm / min for 30 minutes to obtain a precipitate, and the precipitate was added to water for washing; the centrifugation and washing steps were repeated three times, and the precipitate was dispersed in water to obtain ferroferric oxide (Fe 3 O 4 ) nanoparticle suspension, in which Fe 3 O 4 The concentration of nanoparticles was 20 mg / mL;
[0060] (3) 40 mL of Fe 3 O 4 The nanoparticle suspension was added to 10 mL of ZIF-8 / HKUST-1 suspension, and the mixture was heated at 80°C for 12 h to obtain a solid suspension, which was centrifuged at 6000 rpm / min for 10 min, and then ultrasonically washed with water for 3 min. The centrifugation and washing steps were repeated three times. The product was collected and then dried in an oven at 25°C for 24 h to obtain a dried product, which was dispersed in DMF to obtain Fe 3 O 4 Modified ZIF-8 / HKUST-1(Fe 3 O 4 / ZIF-8 / HKUST-1) suspension, in which Fe 3 O 4 The concentration of / ZIF-8 / HKUST-1 was 16 mg / mL;
[0061] (4) Dissolve 20 g of amidated polysulfone (PIPSF) in 100 mL of DMF to obtain a PIPSF solution; then add 100 mL of Fe 3 O 4 / ZIF-8 / HKUST-1 suspensions were mixed and stirred at room temperature to obtain a MOFs-based composite material mother liquor; a semi-continuous spray gun device with a nozzle size of 800 μm was used to make the MOFs-based composite material mother liquor produce droplets and solidify and precipitate in water, and a spherical precipitate was obtained after filtering through a 5 μm nylon filter; that is, a MOFs-based composite pretreatment material was obtained, which was named PIPSF / Fe 3 O 4 / ZIF-8 / HKUST-1.
[0062] The specific synthesis steps of PIPSF are as follows: 20g polysulfone (PSF) is dissolved in 200mL dichloromethane, and then a mixture of 20g chloromethyl ether and 1.5g anhydrous zinc chloride is added dropwise to obtain chloromethylated polysulfone (CMPSF); 10g CMPSF is weighed and dissolved in DMF, and then 200mL of a mixed solution of phthalimide, sodium hydride and DMF (the dosage ratio is 18g:8g:74mL) is slowly added. After heating and condensing and refluxing at 80°C for 10h, the reaction solution is cooled to room temperature; the product is precipitated with a methanol solution, washed repeatedly with water, and dried in a vacuum drying oven at 60°C for 24h to obtain PIPSF;
[0063] Based on the use of MOFs-based composite pretreatment materials that can eliminate CAP interference for the detection of α-SOH in hot pot base, the specific steps are as follows:
[0064] (1) Draw the α-SOH standard curve
[0065] The PIPSF / Fe obtained by the above method can eliminate the interference of CAP 3 O 4 / ZIF-8 / HKUST-1;
[0066] Prepare α-SOH standard solutions of different concentrations; wherein the specific steps of preparing α-SOH standard solutions of different concentrations are: weigh 10 mg of α-SOH into a 5 ml centrifuge tube, add 1 ml of ethanol and sonicate until dissolved, as a standard mother solution; pipette different volumes of the standard mother solution and dilute with ethanol to prepare a series of α-SOH standard solutions of different concentrations (0.1, 0.5, 1, 2, 3, 6, 10 mg / mL), and store at -4°C;
[0067] Then 10 mg of PIPSF / Fe 3 O 4 / ZIF-8 / HKUST-1 was added to water to obtain PIPSF / Fe 3 O 4 / ZIF-8 / HKUST-1 solution;
[0068] Take 10 μL of α-SOH standard solution of different concentrations and mix with 10 μL of PIPSF / Fe 3 O 4 / ZIF-8 / HKUST-1 solution was mixed and incubated at room temperature for 1 min; the solid mixture was separated by magnet adsorption and the solid was collected and redissolved in water to obtain 10 μL of pretreatment standard solution of α-SOH with different concentrations; finally, 10 μL of gold and silver core-shell nanomaterials was used as SERS substrate, mixed with 10 μL of pretreatment standard solution of different concentrations, and 10 μL was added dropwise to the silicon wafer. After drying, the spectrum was scanned by a portable Raman spectrometer to obtain 500-2500 cm -1 Raman spectra within the range, where the Raman spectrometer emits a laser wavelength of 735nm, a fixed laser power of 5mW, an integration time of 4s, and each sample is scanned 10 times to take the average value; at 1630cm -1 The characteristic Raman shift at the position is taken as the quantitative reference peak, the peak intensity value is recorded, and a standard curve is established based on the relationship between the concentration of α-SOH and the peak value at the characteristic Raman shift.
[0069] The specific steps for preparing the gold-silver core-shell nanomaterials are as follows: (a) preparing gold nanorod colloids: in a constant temperature water bath at 25°C, add low-temperature NaBH 4 The solution (0.6 mL, 10 mM) was added to 10 mL of HAuCl 4 (0.25 mM) and CTAB (0.1 M) in a mixed solution, stirred for 2 min and incubated for 2 h to obtain a brown seed solution; CTAB (5 mL, 0.2 M), AgNO 3 (0.15 mL, 4 mM), HAuCl 4 (5mL, 1mM) were mixed in sequence, the solution turned golden yellow, and then ascorbic acid (0.07mL, 0.0788M) was slowly added while stirring to mix the solution evenly, and the solution turned colorless to obtain a gold nanorod growth solution; 0.012mL of the above freshly prepared tea brown seed solution was added to the gold nanorod growth solution, and the solution was stored in the dark at room temperature for 12h, and the solution gradually changed from colorless to dark blue; the dark blue solution was centrifuged at 8000rpm / min for 10min, the supernatant was removed and 20mL of water was added and centrifuged again to remove excess CTAB, and then dispersed in 20mL of water to obtain a gold nanorod colloid; (b) Preparation of gold and silver core-shell: 2mL of gold nanorod colloid and 4mL of CTAC (20mM) were mixed and stirred at 60℃ for 20min; then, 5mL, AgNO 3 (2mM), 5mL of a mixed solution containing CTAC (40mM) and ascorbic acid (0.05M), continued stirring at 60°C for 4h, the solution gradually turned gray-green, and then the synthesized gray-green solution was immersed in ice water for cooling, centrifuged at 4000rpm / min for 10min, washed and redispersed in water to obtain gold-silver core-shell nanomaterials with a concentration of 0.18nM;
[0070] (2) Raman detection of the test liquid
[0071] Weigh 20 g of the spicy hot pot base sample to be tested, add it to 40 mL of ethanol, and place it in an ultrasonic instrument for extraction to obtain a crude extract; centrifuge the crude extract at 3000 rpm / min for 10 min, collect the supernatant, concentrate it on a rotary evaporator, and dilute it with ethanol to obtain a test solution with a volume of 4 mL, which is stored at -4°C for later use; take 10 μL of the test solution prepared above and 10 μL of PIPSF / Fe 3 O 4 / ZIF-8 / HKUST-1 solution was mixed and incubated at room temperature for 1 min; the solid mixture was separated by a magnet and then collected and redissolved in water to obtain 10 μL of sample pretreatment test solution;
[0072] Finally, 10 μL of gold-silver core-shell nanomaterials was used as the SERS substrate, mixed with 10 μL of the pre-treated test solution, and 10 μL was added dropwise to the silicon wafer. After drying, the SERS substrate was heated at 500-2500 cm -1 A portable Raman spectrometer was used to perform spectral scanning within the range, wherein the Raman spectrometer emitted a laser wavelength of 735 nm, a fixed laser power of 5 mW, an integration time of 4 s, and each sample was scanned 10 times to obtain an average value; the obtained spectrum was baseline optimized to obtain a Raman spectrum.
[0073] (3) Quantitative determination
[0074] According to the Raman spectrum of the test liquid obtained in step (2), at 1630 cm -1 The characteristic Raman shift at the position is taken as the quantitative reference peak, and the quantitative reference peak intensity value is recorded. The concentration of α-SOH in the test solution is obtained according to the α-SOH standard curve in step (1), which is recorded as c. The content X of α-SOH in the spicy hot pot base sample is further calculated according to the formula:
[0075]
[0076] X: the content of α-SOH in spicy hot pot base sample, mg / g;
[0077] c: The concentration of α-SOH in the test solution obtained according to the standard curve, mg / mL;
[0078] V 0 : Volume of the test liquid, mL;
[0079] m: Mass of spicy hot pot base sample, g.
[0080] 6. Verification experiment
[0081] The α-SOH content in the spicy hot pot base sample was determined and calculated by high performance liquid chromatography (HPLC) for six test liquids to verify the accuracy of the test results of the method of the present invention. α-SOH was detected by HPLC, and the peak with a retention time of 16.2 to 16.6 min was the target peak. The standard curve of the relationship between the α-SOH concentration and the peak area was drawn. Then 2 mL of the test liquid was taken respectively, filtered through a 0.22 μm organic filter membrane, and then HPLC detection was performed. The α-SOH concentration in the test sample solution was calculated according to the target peak area and the standard curve, and then the α-SOH content in the spicy hot pot base sample was converted according to the formula described in step 5. The α-SOH content determined by the Raman detection method and HPLC is shown in Table 1. The relative errors of the HPLC detection concentration and the Raman spectroscopy detection concentration of different spicy hot pot base samples are less than 10%. The results show that the numbing substance detection method of the present invention can well obtain the α-SOH content in the spicy hot pot base sample, and the detection results are reliable.
[0082] Table 1 Comparison of the results of HPLC and Raman spectroscopy
[0083] Hot pot sample number HPLC detection concentration (mg / g) Raman detection concentration (mg / g) Relative error (%) 1 0.14 0.15 7.1 2 0.47 0.48 2.1 3 0.58 0.56 3.4 4 1.35 1.34 0.7 5 0.134 0.13 3.0 6 0.09 0.09 0
[0084] Note: The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the technical solution. Those skilled in the art should understand that many other modifications and implementation methods can be designed. These modifications and implementation methods do not depart from the purpose and scope of the technical solution and will fall within the scope and spirit of the principles disclosed in this application.
Claims
1. A method for preparing a MOFs-based composite pretreatment material for eliminating CAP interference, characterized in that: Here are the steps: (1) adding the MOFs material to methanol for ultrasonic washing, collecting the solid material by centrifugation after washing, and drying it. The dried product is redispersed in methanol to obtain a metal organic framework suspension, which is recorded as suspension A; (2) dissolving an iron salt in deoxygenated pure water and stirring to obtain an iron salt solution, then adding ammonia water dropwise to the iron salt solution, and continuing to stir after the addition to obtain a dispersion, the obtained dispersion is centrifuged to obtain a precipitate, and after washing and centrifugation, the precipitate is dispersed in water to obtain a magnetic nanoparticle suspension, which is recorded as suspension B; (3) adding suspension A to suspension B, and heating the mixture to obtain a solid suspension; collecting the solid suspension by centrifugation and ultrasonic washing, and then drying the solid suspension to obtain a dried product, which is dispersed in N,N-dimethylformamide to obtain a metal organic framework suspension modified with a magnetic material, which is recorded as suspension C; (4) First, amidated polysulfone is dissolved in DMF to obtain a PIPSF solution; then the suspension C is added and mixed, and stirred at room temperature to obtain a MOFs-based composite material mother liquor; a spray gun device is used to make the MOFs-based composite material mother liquor produce droplets and solidify and precipitate in water, and a spherical precipitate is obtained after filtering; that is, a MOFs-based composite pretreatment material is obtained.
2. The method for preparing a MOFs-based composite pretreatment material for eliminating CAP interference according to claim 1, characterized in that: In step (1), the MOFs material is one or more of HKUST-1, ZIF-67, ZIF-8, Fe-BTC or MIL-101 (Fe); the particle size of the MOFs material is 0.1 to 5 μm; The ultrasonic washing time is 1 to 3 minutes; the centrifugal conditions are 3000 to 8000 rpm / min, 5 to 10 minutes; the drying conditions are: 30 to 60° C., 6 to 12 hours; the concentration range of the suspension A is 0.1 to 10 mg / mL.
3. The method for preparing a MOFs-based composite pretreatment material for eliminating CAP interference according to claim 1, characterized in that: In step (2), the iron salt is one of ferrous chloride tetrahydrate or ferric chloride hexahydrate or a mixture of the two; the concentration of the ammonia water is 20% to 30%; the dosage ratio of the iron salt, deoxygenated pure water, ammonia water and water is (1 to 2) g: (40 to 50) mL: (5 to 10) mL: (40 to 50) mL; and the concentration range of the suspension B is 10 to 30 mg / mL.
4. The method for preparing a MOFs-based composite pretreatment material for eliminating CAP interference according to claim 1, characterized in that: In step (2), the stirring temperature condition for obtaining the iron salt solution is 35° C.; the stirring time is 2 to 3 hours; the centrifugation conditions are 15000 rpm / min, 10 to 30 minutes; and the washing conditions are: adding the precipitate into water for washing.
5. The method for preparing a MOFs-based composite pretreatment material for eliminating CAP interference according to claim 1, characterized in that: In step (3), the dosage ratio of the suspension A to the suspension B is (30-40) mL: (10-20) mL; the concentration range of the suspension C is 10-20 mg / mL; The heating temperature is 50-100°C and the time is 10-20h; the centrifugal conditions are: the rotation speed is 3000-6000r / min and the time is 10-15min; the operation of ultrasonic washing is: adding the precipitate after centrifugation into water for ultrasonic cleaning; the drying conditions are: 25°C, 24h.
6. The method for preparing a MOFs-based composite pretreatment material for eliminating CAP interference according to claim 1, characterized in that: In step (4), the amount ratio of the amidated polysulfone to N,N-dimethylformamide is (10-20) g:100 mL; the volume ratio of the PIPSF solution to the suspension C is (1-5):(1-10); the stirring time at room temperature is 12-24 h; the condition for the MOFs-based composite material mother liquor to produce droplets is: specifically, droplets are produced by a semi-continuous spray gun device with a nozzle size of 800 μm; the operation of obtaining the spherical precipitate is: filtering using a 5 μm nylon filter.
7. Use of the MOFs-based composite pretreatment material prepared according to any one of claims 1 to 6 for detecting α-SOH in hot pot soup base, characterized in that: Here are the steps: (1) Draw the α-SOH standard curve: First, α-SOH standard solutions of different concentrations are prepared; then the prepared MOFs-based composite pretreatment material is added into water to obtain a MOFs-based composite pretreatment material solution; V1 volumes of α-SOH standard solutions with different concentrations were taken respectively, and mixed with V2 volumes of MOFs-based composite pretreatment material solutions, and the mixed solutions were incubated at room temperature; after incubation, the mixtures were separated by a magnet, and the mixtures were collected and redissolved in water to obtain pretreatment standard solutions with different concentrations of α-SOH; finally, V4 volumes of gold-silver core-shell nanomaterials were used as SERS substrates, and the mixed solution mixed with V3 volumes of pretreatment standard solutions was dripped onto a silicon wafer, and after drying, a portable Raman spectrometer was used to perform spectral scanning to obtain a Raman spectrum, and the characteristic Raman shift was used as a quantitative reference peak, and the characteristic peak intensity value I was recorded, and a standard curve was established based on the relationship between the concentration of α-SOH and the peak value at the characteristic Raman shift; (2) Raman detection of samples to be tested: The spicy hot pot base sample to be tested is weighed, and the mass is recorded as m. V0 volume of ethanol is added, and the sample is placed in an ultrasonic instrument for extraction to obtain a crude extract; after centrifuging the crude extract, the supernatant is collected, concentrated by a rotary evaporator, and diluted with ethanol to obtain a test solution, which is stored at low temperature for later use; V1 volume of the test solution is mixed with V2 volume of MOFs-based composite pretreatment material solution, and incubated at room temperature; after incubation, the solid mixture is separated by a magnet, and the solid mixture is collected and redissolved in water to obtain a pretreated test solution; finally, V4 volume of gold and silver core-shell nanomaterials is used as a SERS substrate, mixed with V3 volume of the pretreated test solution, and then dripped onto a silicon wafer, and after drying, a portable Raman spectrometer is used to perform spectral scanning, and the obtained spectrum is baseline optimized to obtain a Raman spectrum; (3) Quantitative determination: According to the Raman spectrum of the test liquid obtained in step (2), the characteristic Raman shift is used as the quantitative reference peak, the quantitative reference peak intensity value is recorded, and the concentration of α-SOH in the test liquid is obtained according to the α-SOH standard curve of step (1), which is recorded as c, and the content X of α-SOH in the spicy hot pot base sample is further calculated according to the formula: X: the content of α-SOH in spicy hot pot base sample, mg / g; c: The concentration of α-SOH in the test solution obtained according to the standard curve, mg / mL; V0: volume of the liquid to be tested, mL; m: Mass of spicy hot pot base sample, g.
8. The use according to claim 7, characterized in that In step (1), the concentration of the MOFs-based composite pretreatment material solution is 0.1 to 10 g / mL; the α-SOH standard solution uses ethanol as a solvent and has a concentration range of 0.1 to 10 mg / mL; the concentration of the gold and silver core-shell nanomaterials is 0.1 to 0.5 nM; the volume ratio of V1, V2, V3 and V4 is 1:(1 to 3):1:1; the collected solid is redissolved in water to obtain pretreatment standard solutions of different concentrations of α-SOH in a concentration range of 0.1 to 10 g / mL.
9. The use according to claim 7, characterized in that: In step (1), the amount added to the silicon wafer is 1 to 10 μL; the incubation time at room temperature is 1 to 10 min; the quantitative reference peak is 1630 cm -1 , which is generated by the vibration of unsaturated fatty chains; the parameters of the portable Raman spectrometer are as follows: the Raman spectrometer emits a laser wavelength of 735nm, a fixed laser power of 5mW, and a scanning range of 500-2500cm -1 The integration time was 1 to 10 s, and each sample was scanned 10 times to take the average value.
10. The use according to claim 7, characterized in that The dosage ratio of the spicy hot pot base sample to ethanol in step (2) is m:V0=(10-20)g:(20-60)mL; the volume ratio of V1, V2, V3 and V4 is 1:(1-3):1:1; the dosage added dropwise to the silicon wafer is 1-10 μL; The extraction time is 5 to 20 minutes; the centrifugation conditions of the crude extract are: 1000 to 3000 rpm / min, the time is 3 to 10 minutes; the low temperature storage condition is -4°C; the incubation time at room temperature is 1 to 10 minutes; the parameters of the portable Raman spectrometer are as follows: the Raman spectrometer emits a laser wavelength of 735nm, the fixed laser power is 5mW, and the scanning range is 500 to 2500cm -1 The integration time was 1 to 10 s, and each sample was scanned 10 times to take the average value.
Citation Information
Patent Citations
Hydroxysanshool rapid detection method based on surface enhanced Raman spectroscopy
CN111220592A
Rapid ultra-sensitive detection method for capsaicin in illegal cooking oil based on surface enhanced Raman spectroscopy combined with molecular derivatization technology
CN112540071A
Preparation method of surface enhanced Raman spectrum substrate material for detecting sanshool in hotpot condiments
CN112540072A